$$\left( {\overline N ,Δ λ } \right)$$ - Salwa Salwa; Qurratul Aini; Ni Wayan Switrayni (Jurnal Matematika, 2022)
Sequence spaces is one of interesting topic of analysis research. Some of that are convergent and bounded sequence. In this paper we define some releated BK spaces (N̅,Δλ) ∞, (N̅,Δλ), dan (N̅,Δλ)O some characteristics releated to them. Moreover we determine their β-dual.